3d-4f coupling and multiferroicity in frustrated Cairo Pentagonal oxide DyMn2O5. Issue 1 (December 2017) - Chattopadhyay, S.; Petit, S.; Ressouche, E.; Raymond, S.; Balédent, V.; Yahia, G.; Peng, W.; Robert, J.; Lepetit, M.-B.; Greenblatt, M.; Foury-Leylekian, P.
Abstract In solid state science, multifunctional materials and especially multiferroics have attracted a great deal of attention, as they open the possibility for next generation spintronic and data storage devices. Interestingly, while many of them host coexisting 3d and 4f elements, the role of the coupling between these two magnetic entities has remained elusive. By means of single crystal neutron diffraction and inelastic neutron scattering experiments we shed light on this issue in the particular case of the multiferroic oxide DyMn2 O5 . This compound undergoes a first order magnetic transition from a high temperature incommensurate phase to a low temperature commensurate one. Our investigation reveals that although these two phases have very different magnetic structures, the spin excitations are quite similar indicating a fragile low temperature ground state with respect to the high temperature one. Such a rare scenario is argued to be a manifestation of the competition between the exchange interaction and 4f magnetic anisotropy present in the system. It is concluded that the magnetic structure, hence the ferroelectricity, can be finely tuned depending on the anisotropy of the rare earth.